Effect of different filler on the strength of interlocking block beam - Salman, Shaari (2014)
Interlocking block beam can replace normal beam in conventional construction method as a lintel in real construction. The interlocking block system may not solved all of the construction problems but this system does resolve a lot of problem associated with conventional method construction. The main feature of the interlocking block is the replacement of mortar layers commonly used in bonded masonry with interlocking keys (S. F. Omar, 2009). The objective of this study is to determine the ultimate flexural strength of interlocking block beams with two type of fillers, mortar and mortar with superplasticizer and the best arrangement of the interlocking blocks in the production of the beam samples by comparing with the normal concrete beam. A four point bending test is conducted to all five beam samples to determine the properties of the beams including strength, deflection and strain. From the collected data, the interlocking block beam samples have higher flexural strength reading than the control beam sample except one of them. The best filler for the interlocking block beam is mortar with superplasticizer based on the results gathered. All experimental and theoretical results were discussed in this study.